Dynamics of Clinical, Laboratory, and Morphostructural Parameters in Patients with Infected Pancreatic Necrosis Associated with Diabetes Mellitus (Texas Journal of Medical Science, 2026)
In this article, the authors analyze the dynamics of clinical, laboratory, and morphostructural parameters in patients with infected pancreatic necrosis (IPN) associated with diabetes mellitus (DM). Clinical studies were conducted in 62 patients with IPN and concomitant DM. The significance of clinical signs, laboratory parameters, instrumental diagnostic methods, and morphostructural indicators in patients with IPN associated with DM was evaluated. Overall, the authors conclude that a comprehensive assessment of clinical, laboratory, and morphostructural changes in patients with IPN and concomitant DM is accompanied by an increasing systemic inflammatory response, pronounced organ dysfunction, and progression of destructive foci during the first 1-3 days of the disease, followed by partial stabilization of the patients' condition by the 10th day as a result of ongoing comprehensive treatment. The study demonstrated that conventional therapeutic approaches do not ensure timely prevention of disease progression in patients with IPN associated with DM